Principles and management of clogging in micro irrigation - Goyal, Megh Raj; Chavan, Vishal K; Tripathi, Vinod K (Innovations and challenges in micro irrigation, 2015)
"Micro irrigation, also known as trickle irrigation or drip irrigation or localized irrigation or high frequency or pressurized irrigation, is an irrigation method that saves water and fertilizer by allowing water to drip slowly to the roots of plants, either onto the soil surface or directly onto the root zone, through a network of valves, pipes, tubing, and emitters. It is done through narrow tubes that deliver water directly to the base of the plant. Clogging is a menace in the success of drip irrigation system, and the situation is more complex under subsurface drip irrigation. Irrigation planners and engineers have found a variety of innovative methods to help to minimize clogging. In this book emphasis is on the implications of micro irrigation clogging, especially under the subsurface placement of laterals. The book offers remedies to decrease clogging and methodologies to improve the performance of micro sprinklers. This valuable resource plans to address this critical problem, covering o challenges in clogging under subsurface drip irrigation; principles, practices and management of emitter clogging; efficiency of acidification for unclogging of emitters; performance characteristics of micro sprinklers. The book will serve as a reference manual for professionals in biological and civil engineering, horticulture, soil and crop science, and agronomy, as well as for graduate and undergraduate students in related fields. It will be a valuable reference for professionals who work with micro irrigation/wastewater and water management, for technical agricultural centers, irrigation centers, agricultural extension services, and other agencies that work with micro irrigation programs."--